Pengaruh Pemanfaatan Rumput Laut Gracilaria Edulis dalam Pakan terhadap Kinerja Ayam Fase Pullet (The Influence of Seaweed Gracilaria Edulis in the Diets on the Performance of Pullet) - Wiesje Martha Horhoruw; Wihandoyo (Wihandoyo); Tri Yuwanta (Buletin Peternakan, 2009)
The research was conducted to analyze the effect of seaweed Gracilaria edulis in the diets on the performance of pullet. One hundred and twenty six Lohmann Brown Strain pullets of 14 weeks old were divided into seven seaweed diet treatments. The treatment diets were R0, R1, R2, R3, R4, R5, and R6 contentaining 0.00; 2.50; 5.00; 7.50; 10.00; 12.50 and 15.00 of seaweed, there was three replications, six pullets of each. The collected data were feed consumption, weights and ages of sexual maturity, feed conversion ratio, weight of egg and Iodine content in the egg. The collected data were analyzed by analysis of variance of one way classification, followed by Duncan’s New Multiple Range Test (DMRT). The results showed that the treatments had not significant differences on feed consumption, body weight at sexual matuarity, feed conversion ratio, but significans (P<0.05) on ages at sexual matuarity and egg yolk color (P<0.01). Feed consumption were 80.94 g/chicken/day; 81.02 g/chicken/day; 80.95 g/chicken/day; 81.43 g/chicken/day; 81.69 g/chicken/day; 82.25 g/chicken/day and 82.72 g/chicken/day, body weight at sexual matuarity1898.56 g; 1977.78 g; 1947.78 g; 1947.78 g; 1949.78 g; 1981.67 g; 1949.44 g, FCR 5.78; 5.35; 5.45; 5.08; 5.57; 5.86 and 6.25, egg yolk color 10.23; 11.27; 11. 83; 12.11; 12.44; 12.44 and 12.83 for R0, R1, R2, R3, R4, R5, and R6 respectively. Egg weights were 51.25 g; 54.50 g; 50.89 g; 51.66 g; 51.36 g; 51.36 g and 50.83 g, for R0, R1, R2, R3, R4, R5, and R6 repectively. There had not significant differences on content of egg yolk iodine were 0.47 ppm; 0.48ppm; 0.50 ppm; 0.52 ppm; 0.55 ppm; 0.56 ppm and 0.60 ppm. It was concluded that the use of seaweed Gracilaria edulis until 15.00% in the diet did not decrease the performance of pullet phase and increased egg yolk color, also did not increase iodine in the yolk.(Key words: Seaweed Gracilaria edulis, Diets, Chicken’s work, Pullet phase)